Investigation into the mechanisms of hyperalgesic priming - Spalton, James Andrew (2017)
Chronic pain is a major clinical problem that affects approximately 40% of the UK population. Understanding the mechanisms that underpin the development and maintenance of chronic pain permits more focused research and identification of potential targets for new therapies. Hyperalgesic priming models the transition from acute to chronic pain. Subcutaneous inflammogens applied 72hrs apart induce a long-term hyperalgesia to mechanical stimulation that outlasts the resolution of the systemic swelling. The aim of this thesis was to investigate the underlying mechanisms of this phenomenon. Two versions of hyperalgesic priming were initially assessed; carrageenan-induced and TNFα induced. The rats pre-treated with carrageenan (primed) (1%, 5μl) showed significantly reduced paw withdrawal thresholds post-intraplantar injection of PGE2 (1μg, 5μl), these were maintained up to 7 days post-injection compared to saline pre-treated (unprimed). Rats pre-treated with TNFα (100ng, 5μl) also showed maintained reductions in PWTs post-PGE2, this however was not significantly lower than saline unprimed rats. To investigate changes in immune cell populations within the peripheral injury site, skin samples collected from carrageenan-primed rats after PGE2 injection showed increased numbers of macrophages compared to saline-saline controls. Ionized calcium-binding adaptor protein (IBA1) immunostaining of the spinal cord showed that there were increased numbers of microglia in the dorsal horn in unprimed rats compared to carrageenan-primed rats. There were alterations in the presence of plasma lipid mediators of inflammation determined using mass spectroscopy in primed compared to unprimed rats. Unprimed rats having a higher level of anti-inflammatory mediators including PGE2 EA and 18-HEPE suggests an alteration in production of inflammatory mediators due to hyperalgesic priming. To evaluate the involvement of sub-sets of primary afferent neurones in priming, sensory nerve blockade using the local anaesthetic QX-314 and capsaicin or QX-314 and flagellin were administered before or after intraplantar injection of PGE2 to selectively block Aβ and C nerve fibres. The injection of QX-314 + capsaicin or QX-314 + flagellin inhibited the PGE2 induced reduction in PWTs however was unable to prevent the establishment of chronic pain. The injection of QX-314 + capsaicin in rats with established chronic pain inhibited the reduction in PWTs however the effect was only seen to last up to 4h post-injection. QX-314 + flagellin partially inhibited the reduction in PWTs up to 2h. These data showed that hyperalgesic priming is mediated by the activation of both C-fibres and partially by Aβ fibres. To assess input changes in CNS processing of primary afferent fibres spinal electrophysiological recordings of wide dynamic range (WDR) neurones in lamina V were performed. These data showed a 300% increase in firing in response to low threshold mechanical stimulation after the intraplantar injection of PGE2. There were no differences observed in WDR firing between primed and unprimed rats post-PGE2. Finally the role of the resolvin resolution pathway was investigated in preventing and reversing hyperalgesic priming. Aspirin-triggered resolvin D1 precursor 17-R-HDoHE has been shown to reduce inflammatory pain. 17-R-HDoHE (300ng, 300μl) was systemically administered before or after PGE2 injection in carrageenan-primed rats. It was shown that administration of 17-R-HDoHE prior to PGE2 significantly (p<0.01) inhibited the sustained reduction in PWTs in primed rats. However systemic administration of 17-R-HDoHE after PGE2 in primed rats had no effect on PWTs. These data show an alteration in the responsiveness of primed rats to the activation of resolvin mediated resolution. Changes in microRNA (miRNA) has been linked to alterations in gene expression in different pain states. To investigate miRNA changes in chronic pain. The L4, L5 and L6 DRGs were collected. There were measured increases in miR-100 and miR-125b during carrageenan induced acute pain and hyperalgesic priming induced chronic pain post-PGE2. Pre-treatment with 17-R-HDoHE was shown in inhibit the up-regulation of miR-100 and miR-125b in DRGs of primed rats. This demonstrated that alterations in the regulation of genes during acute pain may also influence changes during chronic pain. This thesis demonstrates the potential involvement of several altered cellular processes that contribute to the induction and maintenance of long-term hyperalgesia by hyperalgesic priming. I observed decreases in numbers of microglia within the dorsal horn of primed rats. Hyperalgesic priming induced chronic pain requires activity within of both C and Aβ fibre primary afferent populations of sensory neurons. The firing rate of WDR neurones to mechanical stimulation was shown to be increased post-PGE2 intraplantar injection however the increase was not maintained in primed rats. Levels of miR-100 and miR-125b were found to be increased during periods of acute and chronic pain and were found to be inhibited by resolvin treatment. Finally resolvin pre-treatment inhibited the generation of hyperalgesic priming induced chronic pain, but to reverse established pain.